Change of Pore-Fracture Structure of Anthracite Modified by Electrochemical Treatment Using Micro-CT - Xianfa Kong; Junqing Guo; Tianhe Kang (Advances in Materials Science and Engineering)
The electrochemical method can strengthen gas desorption and seepage from coal. The study on change of the pore-fracture structure of coal after electrochemical modification can help to reveal the mechanism. Anthracite was modified by the electrochemical method using our own self-developed experiment apparatus. The pore-fracture structure of modified samples was measured by micro-CT. Combined with the Matlab software, its characteristics such as pore number, porosity, and average pore diameter were analyzed. The results show that (1) the number of fractures in modified coal samples increases. The shape of new fractures in samples in the anodic and cathodic zones was irregular voids and striola, respectively. The effect of electrochemical treatment on the section of samples close to the electrode is relatively obvious. (2) With increasing pore size, the number of pores in samples changes according to negative exponential rules. After electrochemical modification, the porosity of modified samples in the anodic zone increases from 11.88% to 31.65%, and the porosity of modified samples in the cathodic zone increases from 12.13% to 36.71%. (3) The main reason for the increase in the number of pores of coal samples in the anodic and cathodic zones is the treatment of electrolytic dissolution of minerals and electrophoretic migration of charged particles, respectively.